Pressing Temperature Effect on the Properties of Medium Density Particleboard Made with Sugarcane Bagasse and Plastic Bags - Nayra Diniz Nogueira; Carolina Rezende Pinto Narciso; Adriele de Lima Felix; Rafael Farinassi Mendes (Materials Research, 2022)
The objective of this work was to evaluate the effects of different pressing temperatures on the physical and mechanical properties of Medium Density Particleboard (MDP) manufactured with sugarcane bagasse and waste plastic bags.The temperatures of 160, 180, 200 and 220ºC were evaluated for the panels pressing. The panels were produced with a nominal density of 0.70 g/cm3, a face/core ratio of 40:60, 12% urea-formaldehyde adhesive for the faces and 8% for the core. The panels were evaluated for properties of density, compaction ratio, humidity, water absorption after two and twenty-four hours (WA2h and WA24h), thickness swelling after 2 and 24 hours of immersion in water (TS2h and TS24h), module of rupture (MOR) and module of elasticity (MOE) in static bending, internal bonding, janka hardness and screw pulling. There was no significant effect of pressing temperature on density, MOR, MOE, internal bonding and janka hardness of the panels.The pressing temperature significantly influenced the properties of WA, TS and screw pullout, promoting a decrease in the mean values of WA2h, WA24h, TS2h and TS, and an increase in screw pullout resistance. The temperature of 220°C resulted in MDP panels with sugarcane bagasse and residual plastic bags of better quality.